Plasmonics on a Neural Implant: Engineering Light–Matter Interactions on the Nonplanar Surface of Tapered Optical Fibers (Advanced Optical Materials 2/2022). Issue 2 (18th January 2022) - Pisano, Filippo; Kashif, Muhammad Fayyaz; Balena, Antonio; Pisanello, Marco; De Angelis, Francesco; de la Prida, Liset M; Valiente, Manuel; D'Orazio, Antonella; De Vittorio, Massimo; Grande, Marco; Pisanello, Ferruccio
Abstract : In article number 2101649, Filippo Pisano and co‐workers demonstrate a first step towards implantable multimodal plasmonic neural interfaces. This was achieved by integrating highly‐curved plasmonic nanostructures on a tapered optical fiber in order to engineer the spectral and angular patterns of optical emission and collection, with applications to fluorescence and Raman spectroscopy. [Cover image: artwork by Antonio Balena.]